EFEKTIVITAS PENGGUNAAN MEDIA PREPARAT MELALUI PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP PENINGKATAN KECAKAPAN BERPIKIR RASIONAL SISWA - Ema Rochmaniar Suprayitno; pramudiyanti pramudiyanti; rini rita marpaung (Universitas Lampung, 2013)
Rational thinking skill is one of the result learning demand which should be owned by each student. The result of observation in class VIII of Junior High School 19 Bandar Lampung was known that student’s rational thinking skill didn’t develop in an optimal fashion yet. Objective of this research is have cognize of efectivity of using biology slide media through Jigsaw’s cooperative learning type in enhancement of student’s rational thinking skill in Plant Tissue Structure and Function Mainly Description. This research is a quasi experiment with pretest-postest non equivalent group design. Samples of research are student class VIII G and VIII H which are chosen by cluster random sampling. Quantitative datas are obtained from average of pretest, posttest, and N-gain which are analyzed statistically using t-testand U-test in 5% confidence degrees through program of SPSS 17. Qualitative datas include student’s learning activities and conceptions of using of biology slide media through Jigsaw’s cooperative learning type in enhancement of student’s rational thinking skill in Plant Tissue Structure and Function Mainly Description.. Result of research shows that largely student give positive conceptions of using of biology slide media through Jigsaw’s cooperative learning type. But then, this case isn’t in line with learning result was gotten by student. The average of student’s rational thinking skill improvement in class experiment is lower than control (experiment=14,63%; control=22,59%). Beside that, percentage average of improvement of student’s activities in all observed aspects in class experiment is also lower than control (experiment=66,67%; control=79,17%). Thereby, using of biology slide media through Jigsaw’s cooperative learning type isn’t effective to enhance of student’s rational thinking skill in Plant Tissue Structure and Function Mainly Description. Keywords: Jigsaw’s cooperative learning type, rational thinking skill, Plant Tissue Structure and Function.